Application of C4.5 Classification in Improving Recitation Fluency in Students - Sisca Yuliantina; Betha Nurina Sari (Paradigma, 2023)
Fluency in reciting the Koran is learning the recitation of the Qur'an in a tartil way. Based on the observations of researchers, the learning of tajwid in recitation and at school has not been effective so far. Because of this, both teachers and students at recitation or at school need improvement by finding out what can increase fluency in reciting the Koran and what has the most influence on improving fluency. So this study aims to improve the fluency of the Koran in students. The research method used is the Decision Tree data mining classification method with the C4.5 algorithm. The results of data processing with the C4.5 algorithm using the Rapidminer tools are attribute C1(fluency) being the most influential attribute for increasing students' reading fluency and performance data obtained with an accuracy of 83,33%.